Comunicação e consumo da cultura terapêutica: reflexividade, aconselhamento e empreendedorismo de si nos discursos da Escola de Você e The School of Life - Quintal, Priscila Tuna (2016)
Based in the correlations between communication and consumption, this paper aims at analyzing and understanding how the subjectivities are currently targeted by educational initiatives identified with the therapy culture. The object chosen for this study is the audiovisual material produced by two companies self-nominated schools, Escola de Você The School of You and The School of Life . Although they have different audience and operate in different countries, both are similar in their action proposals for committing to improve the life of their students referred to as consumer apprentices - through their classes. In order to analyze how these discourses are articulated, one used a methodological theoretical umbrella that emphasizes three main approaches which define our analysis process: affective cartography, critical discourse analysis and film analysis. Such analytical approaches allow us to organize and map the material available to subsequently reach the delimitation of the corpus; take a critical look beyond the speeches, and ultimately, read the audiovisual elements that make up the selected films. The main affections brought by the videos start the chapters, and then the corpus of the videos is used to reach the theory. The theoretical reflections are based in three basic concepts: modern reflexivity, counseling and itself entrepreneurship, as proposed by the title. Although such schools aim at teaching about life, they clearly lack of what it takes to a real formation of the individual and autonomy. What they actually bring up is a pathological consumer that transcends the status of apprentice to be trained to identify problems in their lives and resolve them with the help of expert systems.